2011
DOI: 10.1038/eye.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

The use of propranolol in the management of periocular capillary haemangioma—a systematic review

Abstract: Capillary haemangioma or infantile haemangioma (IH) is the most common congenital vascular tumour in the periocular region. Several treatment modalities have been documented, with variable degree of success. Propranolol has recently been reported to be an effective and safe alternative. The aim of this systematic review is to examine the evidence base for the use of propranolol administered orally in the management of periocular capillary haemangioma, and use this information to guide future research. A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…It seems to be effective in halting growth and diminishing size of haemangiomas not only during the proliferative phase but also, to a lesser extent, once growth has been completed . Studies of propranolol use in ulcerated haemangiomas, periocular haemangiomas, airway haemangiomas and liver haemangiomas support its use in these specific clinical settings …”
Section: Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…It seems to be effective in halting growth and diminishing size of haemangiomas not only during the proliferative phase but also, to a lesser extent, once growth has been completed . Studies of propranolol use in ulcerated haemangiomas, periocular haemangiomas, airway haemangiomas and liver haemangiomas support its use in these specific clinical settings …”
Section: Treatmentmentioning
confidence: 96%
“…If visual compromise is detected or suspected, therapy is indicated. Systemic and intralesional corticosteroids, surgical excision and laser have been used in the past, but propranolol has now become a first‐line treatment in this setting . For small superficial haemangiomas of the eyelid without associated visual compromise, topical timolol maleate shows promise as a safe, new treatment based on case series and reports .…”
Section: Complications and Managementmentioning
confidence: 99%
“…first reported that propranolol was successful in treating IH . Since then, subsequent reports demonstrated involution of problematic hemangiomas treated with systemic propranolol . Propranolol, which is superior to corticosteroids at controlling the growth phase of complicated IH, has gradually taken the place of corticosteroids and become the first‐line therapy for complicated hemangiomas in many centers …”
Section: Introductionmentioning
confidence: 99%
“…The main cardiac side effects of propranolol are severe bradycardia, hypotension, and poor cardiac contractility. These side effects are dose related and are uncommon at the oral dosage used for IH (typically 2 mg/kg/day), with the rare occurrence of symptomatic hypotension or other parameters when measured . The main noncardiac side effects of propranolol treatment are hypoglycemia and bronchospasm in patients with reactive airway disease.…”
mentioning
confidence: 99%